Results of a non-interventional multicenter study of management of patients with non-radiological axial spondyloarthritis in real-life clinical practice in the Russian Federation (NiSpAR) - T. V. Dubinina; A. M. Lila; E. V. Kvasova; E. M. Agafonova; I. A. Andrianova; L. V. Ivanova; D. V. Yurk; N. A. Garaeva; E. Y. Akulinushkina; A. N. Vedekhina; I. B. Bashkova; S. A. Lapshina; et al. (Современная ревматология, 2024)
NiSpAR is a non-interventional, multicenter study whose aim was to describe a cohort of patients with non-radiological axial spondyloarthritis (nr-axSpA) and approaches to its diagnosis in the Russian Federation.Material and methods. The study involved 20 research centers in different regions of the Russian Federation. The work consisted of two phases: retrospective data collection 12 months before enrolment in the study and prospective observation of patients in whom the diagnosis of nr-axSpA was confirmed (104 weeks).The study included 272 patients who met the inclusion and exclusion criteria (Full Analysis Set, FAS). The mean age of the FAS-population was 38.7±11.0 years. The diagnosis of nr-axSpA was confirmed in 159 (58.5 %) of the 272 patients. Of the remaining 113 (41.5%) participants, 57 (50.4%) did not have the information required to confirm the diagnosis, 34 (30.1%) did not have pelvic radiographs, and 22 (19.5%) did not fulfil the ASAS criteria for nr-axSpA.Results and discussion. The mean age of patients with nr-axSpA was 37.6±10.4 years, more than half of them (52.8%) were women. The median disease duration was 36 [12; 80] months. In half of the patients the disease duration was more than 2 years, in more than one third – less than 2 years. The median CRP and ESR values were 5.0 [2.0; 12.0] mg/l and 11.0 [5.0; 18.0] mm/h, respectively. The BASDAI averaged 3.5±2.0 and was >4 in more than half of the cases (64.2%). The mean ASDAS-CRP value reached 2.6±1.1. Only 1 in 5 participants (20.8%) had low axSpA activity, while in 61.1% it was high (44.7%) or very high (16.4%). An inactive state was found in a small number of patients (9.4%). Twenty two (13.8%) patients had treatment with biologic disease-modifying antirheumatic drugs (bDMARDs) in anamnesis, and 21 (13.2%) patients were still taking them.Conclusion. The results of the retrospective phase of the study show that in real-life clinical practice in the Russian Federation there is a continued positive trend towards improving the diagnosis of nr-axSpA. The median duration of the disease at the time of enrolment in the study was 3 years. The frequency of use of magnetic resonance imaging has increased by more than 1.8 times. At the same time, practitioners still have difficulties in establishing the diagnosis of nr-axSpA and a shortage of bDMARDs for treatment of these patients.